SIRT6-mediated transcriptional suppression of MALAT1 is a key mechanism for endothelial to mesenchymal transition. (15th November 2019) - Qin, Wei; Zhang, Longyin; Li, Zhange; Xiao, Dan; Zhang, Yue; Yang, Huan; Liu, Xin; Zhang, Haiying; Chen, Xiaohui; Xu, Chaoqian; Yang, Baofeng; Zhang, Yong
Abstract: Background: Vascular aging has profound effects on cardiovascular diseases. Endothelial to mesenchymal transition (EndMT) is defined as the acquisition of mesenchymal characteristics by endothelial cells (ECs) and has been found induced in a model of ECs aging. However, whether EndMT occurs during aging in vivo, the functional significance of EndMT on vascular biology and the underlying mechanisms remain unknown. Methods and results: In this study, we examined the vascular ECs from young (2 months old) and old (18 months old) mice, and demonstrated that aged ECs underwent EndMT. Moreover, the transwell assay showed that EndMT process was accompanied by increased endothelial permeability. It was found that sirtuin 6 (SIRT6), a nicotinamide adenine dinucleotide + (NAD + )-dependent histone deacetylase, was down-regulated during ECs aging. Knockdown of SIRT6 in young ECs could induce EndMT. Next, we identified five long non-coding RNAs that are enriched in ECs for downstream effector of SIRT6; only metastasis associated lung adenocarcinoma transcript 1 (MALAT1) was significantly up-regulated in aged ECs. Knockdown of SIRT6 could increase MALAT1 levels. Furthermore, the ChIP assay and luciferase reporter gene assay confirmed that SIRT6 bound directly to the promoter region of MALAT1 and suppressed MALAT1 expression. Finally, we demonstrated that MALAT1 mediated aging-induced EndMT through increasing Snail expression. Conclusion: Our study provides in vivo evidence that ECs undergo EndMT during vascular aging, which increases endothelial permeability. SIRT6-mediated transcriptional suppression of MALAT1 is a key mechanism for EndMT. Manipulating EndMT may be considered as a new therapeutic strategy for retarding aging-associated vascular diseases. Graphical abstract: Unlabelled Image Highlights: Endothelial to mesenchymal transition (EndMT) occurs during vascular aging in mice. SIRT6 deficiency is responsible for aging-induced EndMT in endothelial cells. SIRT6 binds to the promoter of MALAT1 and represses MALAT1 expression. Manipulating EndMT may be considered as a new therapeutic strategy for retarding aging-associated vascular diseases.